(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Reading is a fundamental component of language development and plays a crucial role in building both receptive and productive skills. This article examines the role of reading aloud in improving reading fluency, particularly among primary-level learners of English as a foreign language. Drawing on established theories of reading and language acquisition, it highlights how reading aloud supports the development of phonological awareness, vocabulary acquisition, and confidence in oral communication. The paper also discusses interactive read-aloud practices, emphasizing the importance of teacher guidance, scaffolding, and student engagement in meaning-making processes. Furthermore, it explores the differences between first language (L1) and second language (L2) reading, underlining the cognitive and linguistic challenges faced by learners.